Twinning Europe and Asia in Cyberspace: The EU legislation, ASEAN and its transformative power - Kamil Ariadno, Melda; H Bajrektarevic, Anis H (AEI Insights, 2021)
While our troposphere is dangerously polluted, one other space – that of intangible world, created by the interconnected technology – follows the same pattern: a cyberspace. Additionally, our cyberspace becomes increasingly brutalised by its rapid monetisation and weaponisation. It mainly occurs through privacy erosion. How to protect effectively individuals and their fundamental human rights, and how to exercise a right for dignity and privacy? The EU now offers a model legislation to its Member States, and by its transformative power (spillover) to the similar supranational projects elsewhere (particularly ASEAN, but also the AU, OAS, SCO, SAARC, LAS, etc.), and the rest of world.